2022
DOI: 10.34306/att.v4i1.228
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Digitalization On Culinary Msmes On Increasing Sales Turnover During Covid 19 Pandemic

Abstract: This study aims to determine the effect of digital marketing and the use of the marketplace for Culinary MSMEs on increasing sales turnover during the COVID-19 pandemic. The research population is Culinary MSMEs in DKI Jakarta whose number is unknown. Determination of the number of samples by Hair et.al (2014) which is a minimum of 50 culinary traders in Jakarta by sampling using the purposive sampling method, with the following criteria: Respondents are limited to small and micro entrepreneurs (UMK) Culinary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
4
0
9
Order By: Relevance
“…Dalam kegiatan penyebaran kuesioner dilakukan penyebaran kuesioner kepada pelaku UMKM dengan menggunakan (Purnama et al, 2022), maka sampel ditentukan 2. Indikator IT Capability meliputi : Integrasi, Accesibility, Ease to use, Adaptability (Munandar et al, 2022).…”
Section: Metode Penelitianunclassified
“…Dalam kegiatan penyebaran kuesioner dilakukan penyebaran kuesioner kepada pelaku UMKM dengan menggunakan (Purnama et al, 2022), maka sampel ditentukan 2. Indikator IT Capability meliputi : Integrasi, Accesibility, Ease to use, Adaptability (Munandar et al, 2022).…”
Section: Metode Penelitianunclassified
“…Several studies have shown that fuzzy improves accuracy [6], other studies explain that fuzzy models can improve the accuracy and efficiency of diagnosis [7]. Meanwhile, research [8] explains that fuzzy has high accuracy and has an effective performance for classification algorithms. Based on the advantages of fuzzy logic, this logic is often used to help the main method so as to get more optimal results.…”
Section: Fuzzy Algorithm Fuzzymentioning
confidence: 99%
“…In research conducted (Masyhuri et al, 2021) explaining the use of the smartPLS3.0 method, it was found that the use of ICT had a significant effect on company performance, as well as innovations that were not successful in mediating the use of ICT on company performance. While research from (Purnama et al, 2022) also stated that using the MLR method, the results obtained were that the Digital Marketing variable and the use of Marketplace influenced the variable Increase in Sales Turnover partially and significantly in the culinary sector MSMEs. Marketplace to Increasing Sales Turnover simultaneously.…”
Section: Introductionmentioning
confidence: 99%